Deconstructing the Ambiguity of the Right to Build (HGB) over the Right of Management (HPL): Delegitimizing HPL on Non-Vital Land and Reconstructing Land Law in Indonesia - Ibnu Rusdian; Endang Pandamdari; Irene Marianne (Transpublika Publisher, 2026)
The Indonesian land law system faces a fundamental problem in which HGB above HPL does not fully function as an independent land right due to its structural dependency on the administrative authority of the HPL holder. This research aims to examine the ambiguity of the construction of the Right to Build (HGB) over the Right of Management (HPL), to delegitimize the applicability of HPL on non-vital land, and to formulate a land law reconstruction that provides greater legal certainty and independence of rights. This research is normative legal research employing conceptual, statutory, legal theory, and comparative law approaches. Analysis is conducted qualitatively and prescriptively using Jacques Derrida’s legal deconstruction to dismantle the legitimacy of HPL, and Mochtar Kusumaatmadja’s Development Law Theory as the basis for legal reconstruction. The results show that the ambiguity of HGB over HPL stems from the structural dependency of HGB on the administrative authority of the HPL holder, which causes HGB to not fully function as an independent land right. Through the deconstructive approach, it was found that the legitimacy of HPL over non-vital land no longer has a strong public basis, because such land has in fact developed into a stable private or semi-private space. The findings suggest restricting HPL to strategically vital land while transferring non-vital land to a more independent rights regime through partial HPL release, state land reclassification, and stronger HGB holder protections.